2021
DOI: 10.3390/ani11020487
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Identify Pregnancy Failure in Buffalo Cows

Abstract: The aim of this work was to find the best strategy to diagnose pregnancy failures in buffalo. A total of 109 animals belonging to a buffalo herd subjected to a synchronization and artificial insemination (AI) program were enrolled in this study. Blood samples were collected at days 0, 14, 25, 28 and 40 after AI for the determination of progesterone (P4) and pregnancy-associated glycoproteins (PAGs) by the radioimmunoassay (RIA) method. Transrectal ultrasonography was performed on day 25, 28 and 40 after AI to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Based on the area under the curve (AUC), the BUT score may be considered to be uninformative (AUC = 0.50), poorly accurate (0.50 ≤ AUC ≤ 0.70), moderately accurate (0.70 ≤ AUC ≤ 0.90), very accurate (0.90 ≤ AUC < 1) or perfect (AUC = 1). The optimal cut-off was determined using Youden’s index [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the area under the curve (AUC), the BUT score may be considered to be uninformative (AUC = 0.50), poorly accurate (0.50 ≤ AUC ≤ 0.70), moderately accurate (0.70 ≤ AUC ≤ 0.90), very accurate (0.90 ≤ AUC < 1) or perfect (AUC = 1). The optimal cut-off was determined using Youden’s index [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Barile et al [ 11 ] showed that PAGs permitted the discrimination between buffalo that experienced embryonic mortality and those that maintained pregnancy starting from 25 days of gestation, defining the optimal cut-off value for predicting mortality at day 25 and 28 post-AI.…”
Section: Other Livestock Speciesmentioning
confidence: 99%
“…Embryo death can be visibly diagnosed by an undetectable heartbeat; nevertheless, when an embryo with a heartbeat is viewed, there is no indication as to whether or not embryo mortality will occur. Therefore, ultrasonography is not predictive of embryonic mortality [ 11 ]. Thus, new technologies to identify embryonic mortality early after AI may play a key role in management strategies to improve the reproductive efficiency and profitability of dairy farms.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other chemical based methods have also been reported to detect pregnancy in buffaloes and rely on quantification of progesterone (P 4 ) in milk and blood at around day 24 post-AI [ 9 ]. Pregnancy associated glycoproteins (PAGs) have also been reported for pregnancy diagnosis in buffalo with acceptable accuracy around day 25 postbreeding [ 10 ]. Apart from difficulty in conducting chemical-based methods under the field conditions, these methods require repeated sampling and are useful only after maternal recognition of pregnancy that takes place at around day 17 postbreeding [ 11 ].…”
Section: Introductionmentioning
confidence: 99%